Implant-supported mandibular removable partial dentures; patient-based outcome measures in relation to implant position. (December 2016) - Jensen, Charlotte; Raghoebar, Gerry M.; Kerdijk, Wouter; Meijer, Henny J.A.; Cune, Marco S.
Abstract: Objectives: To assess the benefits of implant support to Removable Partial Dentures (RPD) in patients with a bilateral free-ending situation in the mandible and to determine the most favorable implant position: the premolar (PM) or the molar (M) region. Methods: Thirty subjects with a bilateral unbounded posterior saddle received 2 PM and 2 M implants. A new RPD was placed. Implant support was provided 3 months later. Two PM implants supported the RPD. After 3 months the 2 M implants were used or vice versa. Outcome measures included oral health related quality of life (OHIP-NL49), general health status (SF-36), contentment assessed on a Visual Analogue Scale (VAS) and the number of hours that the RPD was worn. Data were collected prior to treatment, 3 months after having functioned with a new RPD and after 3 and 6 months with implant support. Finally, patients expressed their preferred implant position. Results: The general health status (SF-36) was not influenced. OHIP-NL49 values and mean wearing-time were statistical significantly more favorable for ISRPD's, regardless of the implant position. Per day, the ISRPD's were worn 2–3 h more than the unsupported new RPD. Patients' expectations were met as the VAS-scores of anticipated and realized contentment did not reach a statistical significant level (p > 0.05). VAS scores for ISRPD's with M implant support were higher than for PM implant support. Finally, 56.7% of subjects preferred the M implant support, 13.3% expressed no preference and 30% opted for PM implant support. Conclusions: Mandibular implant support favorably influences oral health related patient-based outcome measures in patients with a bilateral free-ending situation. The majority of patients prefer the implant support to be in the molar region. Clinical significance: Patients with a bilateral free-ending situation in the mandible opposed by a maxillary denture benefit from implant support to their mandibular removable partial denture. Most patients prefer this support to be in the molar region.